(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
The aim of the work was to evaluate the features of some physiological indicators of rats with different phenotypes by the activity of the liver monooxygenase system. The experiments were conducted on 100 white male rats. They were divided into fast, medium and slow metabolizers based on nembutal sleep and food and water consumption, as well as diuresis, were studied. The results showed that the distribution in the general population of fast, intermediate and slow metabolizers was in the ratio of 1:1.5:2.5, and that the absolute weight of fast metabolizer rats was lower than that of intermediate and slow metabolizers, and the absolute water consumption and diuresis were higher.